The Meaning of Independent Women in Social Media - Sundah, Pierre Mauritz; Parulian, Nathaniel Antonio; Naha, Rambu (Jurnal Riset Komunikasi, 2024)
Indonesian women’s lives had been challenging at times, leaving little room for them to work. Numerous reasons contribute to these restrictions. One of the influencing elements is that men in Indonesia are given more flexibility to participate in the wider context of society, including being the primary source of producing revenue, but women in Indonesia are forced to play a role as someone who is responsible for household duties. The deeply ingrained patriarchal culture in Indonesia is to blame for this. Women in East Nusa Tenggara are also affected by this social issue, particularly those who reside on Solor Island in East Flores. Due to the poor and inconsistent quality of education, women who live there frequently receive social evaluations from other Indonesians and are stereotyped as being unintelligent, leading to the belief that women can only rely on men. However, there are other things that can be seen on the Instagram account @duAnyam, where women have the chance to become empowered in the production of woven goods, giving them the same opportunities as men who can establish economic and financial independence. Based on this social phenomenon, it is intriguing to do this research in order to understand what independent women lies @duAnyam on Instagram imply. To describe how women perceive their function as independent, typically tied to males, this study will employ qualitative methods and a phenomenological approach. The findings reflect what women mean in terms of their varying perceptions of the intrinsic independence that they possess.